Effect of Nickel Incorporation on Nitrogen-Doped Titania/Zirconia Nanocomposites for Enhanced Visible-Light Photocatalytic Degradation of Phenol - Akhmad Syoufian; Aldino Javier Saviola; Reza Rodhatul Janah; Rina Afifah; Karna Wijaya; Rian Kurniawan; Sri Sudiono; Won-Chun Oh; Wangsa Wangsa (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
The rapid expansion of industrial activities has resulted in the discharge of persistent organic pollutants, such as phenol, into aquatic environments. Nowadays, developing visible-light-responsive photocatalysts for the efficient degradation of such pollutants remains a major environmental challenge. In this study, nickel–nitrogen co-doped titania immobilized on zirconia (Ni,N–TiO₂/ZrO₂) nanocomposites with varying nickel loadings were synthesized and evaluated for phenol photodegradation under visible-light irradiation. Nickel incorporation significantly modified the optical and photocatalytic properties of the materials. The 5% Ni,N–TiO₂/ZrO₂ catalyst exhibited the lowest band gap energy (2.69 eV) compared with N–TiO₂/ZrO₂ (3.03 eV), leading to improved visible-light absorption and enhanced charge transfer. Under the experimental conditions (initial phenol concentration = 10 mg.L⁻¹, catalyst dosage = 100 mg, irradiation time = 120 min), it achieved a phenol removal efficiency of 85.36% with an apparent rate constant of 0.0229 min⁻¹, outperforming N–TiO₂/ZrO₂ (40.72%, 0.0042 min⁻¹). These results confirm that a 5 wt% nickel loading provides the most effective modification, demonstrating a strong synergistic interaction between nickel and nitrogen that enhances photocatalytic activity. The developed Ni,N–TiO₂/ZrO₂ catalyst, therefore, holds significant promise for future applications in water purification and environmental remediation. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).